A simple and adaptable method for cloning genes into transposon vectors using topo and restriction systems for chicken embryo transgenesis - Kirimi, P.; Okumu, Noah; Maingi, J.M.; Ngeranwa, J.; Nyaga, P.; Binepal, Y. (Bio-Protocol, LLC, 2025)
Transposon-based genetic transformation enables stable transgene integration in avian genomes and is increasingly used in the development of transgenic chickens for enhanced disease resistance, productivity, and biopharmaceutical applications. Conventional transformation techniques in avian biotechnology, including viral vectors and primordial germ cell (PGC) manipulation, are limited by biosafety risks, low efficiency, and technical complexity. This protocol outlines a two-step cloning approach for generating transposon-compatible gene constructs suitable for chicken embryo microinjection. Topoisomerase-based (TOPO) cloning is used as the first step due to its ability to directly clone PCR-amplified products without the need for restriction site-engineered primers while simultaneously producing an insert flanked with EcoRI restriction sites. The insert is subsequently transferred into the transposon vector through EcoRI-mediated restriction digestion and ligation. This approach simplifies construct generation by integrating the speed of TOPO cloning with the precision of restriction cloning, while ensuring compatibility with transposon-mediated integration systems. The protocol is efficient, reproducible, and does not require specialized equipment, providing a practical and scalable tool for gene construct assembly in avian transgenesis research.